Evaluation of Timing and Dosage of a Parent-Based Intervention to Minimize College Students’ Alcohol Consumption - Turrisi, Rob (Rutgers University, 2013)
OBJECTIVE: The study evaluated the timing and dosage of a parent-based intervention to minimize alcohol consumption for students with varying drinking histories. METHOD: First-year students (N = 1,900) completed Web assessments during the summer before college (baseline) and two follow-ups (fall of first and second years). Students were randomized to one of four conditions (pre-college matriculation [PCM], pre-college matriculation plus boosters [PCM+B], after college matriculation [ACM], and control conditions). Seven indicators of drinking (drink in past month, been drunk in past month, weekday [Sunday to Wednesday] drinking, Thursday drinking, weekend [Friday, Saturday] drinking, heavy episodic drinking in past 2 weeks, and peak blood alcohol concentration <.08) were used in a latent transition analysis (LTA) to examine a stage-sequential model of drinking. LTA models with dummy-coded intervention variables were used to examine the effects of the intervention conditions on changes in drinking patterns. RESULTS: Results indicated that four patterns of drinking were present at all waves: (a) nondrinkers, (b) weekend light drinkers, (c) weekend heavy episodic drinkers, and (d) heavy drinkers. Results indicated that the PCM condition was most effective at influencing baseline heavy drinkers’ transition out of this pattern to lower risk patterns at first follow-up, whereas the ACM condition was not effective at preventing drinking escalation for baseline nondrinkers at first follow-up. No decay of effects was observed at long-term follow-up for the PCM condition. Finally, the results also indicated that increased dosage of the parental intervention was not significantly associated with either reduction or escalation of use. CONCLUSIONS: The results underscore the value of pre-college parental interventions and targeted efforts to reduce high-risk drinking among college students.